2015
DOI: 10.1016/j.physbeh.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The sweetness and bitterness of childhood: Insights from basic research on taste preferences

Abstract: In this article, we review findings from basic, experimental research on children that suggests the liking of sweet and the dislike of bitter tastes reflects children’s basic biology. Children are born preferring sweet tastes, which attract them to mother’s milk and even act as an analgesic. They prefer higher levels of sweet than do adults, with preferences declining to adult levels during middle to late adolescence, which coincides with the cessation of physical growth. The level of sweetness most preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(170 citation statements)
references
References 83 publications
8
150
1
11
Order By: Relevance
“…The studies identified were also notably all undertaken in children, in whom effects of sweet taste exposure may be difficult to see against a background of strong innate liking (15), and in whom differences in dietary intakes may reflect parenting practices and household food offerings, rather than preferences for specific sensory attributes. Preferences for sweet tastes are also known to reduce with age (2,24), and therefore impacts demonstrated in childhood may not transfer to adulthood (15).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The studies identified were also notably all undertaken in children, in whom effects of sweet taste exposure may be difficult to see against a background of strong innate liking (15), and in whom differences in dietary intakes may reflect parenting practices and household food offerings, rather than preferences for specific sensory attributes. Preferences for sweet tastes are also known to reduce with age (2,24), and therefore impacts demonstrated in childhood may not transfer to adulthood (15).…”
Section: Tablementioning
confidence: 99%
“…Sweet taste is innately rewarding, as characterized by a universal liking for high levels of sweetness in foods and beverages in infancy and childhood (2), and it is possible that high levels of sweetness or sustained exposures to sweet taste help maintain or even promote a generalized desire for sweet(er) foods and beverages in the wider diet. Such a generalized "sweet tooth" could make it challenging for individuals to reduce intakes of free sugars (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in children also indicates that sourness perception is inversely related to acceptance of sourtasting foods (32,79). For sweet and fatty taste, however, the relationship between perception and intake is more complicated and likely is an inverse U-shaped curve, where the optimally preferred concentration varies depending on age and developmental and genetic factors (93).…”
Section: Figurementioning
confidence: 99%
“…O que fez os pesquisadores concluírem uma resposta positiva à estimulação umami e doce [14][15][16][17] .…”
Section: Preferência Genética Ou Ambiental?unclassified
“…Além disso, a alimentação espontânea não é estável de um dia para o outro, o equilíbrio se faz a cada dia. A criança pode ter fome mesmo após terminar a mamadeira, ou ser rapidamente saciada, o que pode causar dificuldades de identificação, pela família, da necessidade alimentar 1,16 .…”
Section: Preferência Genética Ou Ambiental?unclassified